TELAAH MAIN HAKIM SENDIRI (EIGENRICHTING) DALAM ASPEK HUKUM PIDANA DI INDONESIA DAN KAITANNYA DENGAN HAK ASASI MANUSIA - Fitri Wahyuni (JURNAL HUKUM DAS SOLLEN, 2017)
The act of vigilante (eigenrichting) is an act that punishes a party without going through a process in accordance with the law. The Criminal Code does not specifically regulate sanctions for the perpetrator of the vigilante (eigenrichting), but the offender (eigenrichting) can be subject to criminal sanctions as contained in the article on persecution namely article 351 of the Criminal Code, in addition according to the criminal law a person who performs vigilante action (eigenrichting) may be subject to criminal liability if it meets elements of: criminal acts, capable of liability, intent or negligence, and no excuse for forgiveness. If it is associated with human rights, then the act of vigil (eigenrichting) is contradictory to Law Number 39 Year 1999 on Human Rights Article 3 Paragraph (2) which reads "Everyone is entitled to the recognition, guarantee, protection and fair treatment of law as well as obtaining legal certainty and equal treatment before the law.